Analysis influence factors of domination, competency and interpersonal skill in the stakeholder interaction to infrastructure project success - Bayuaji Sanggoro, Heru; Widyaningsih, Nunung; P. K. Bintoro, Bambang (International Journal of Engineering and Technology, 2020)
Project is picture of interaction model from various interests in social communication among the stakeholders. Stakeholders interaction factors can be influenced by domination and competencies beside their interpersonal skills. This research based on samples of respondents from East Java and West Sumatra provinces, Indonesia, which have similar social behavior and socio-cultural strength. Subject of research focused on three main projectâ€™s stakeholders, which will be analyzed by partial least square-structural equation model (PLS-SEM). The result of analysis shows that domination factor has the greatest influence to infrastructures project implementation. It means that influence of feudalism cultural heritage remain affecting to local people character and work culture. However, respondents from East Java consider competency as a significant variable which influences the infrastructure project success. West Sumatera respondents are the opposite, where competency is not a significant variable to the project success directly. Meanwhile, interpersonal skill can be good mediation variable for domination and competency to the project success in the West Sumatra, but it is not good enough to mediate domination to project success in the East Java. Thus, it can be concluded that West Sumatra respondents have a more feudal interaction style than stakeholders in East Java.Â Â